Prospek Bisnis Briket Daun Kering dalam Kegiatan Pendampingan dan Pemberdayaan Masyarakat Surabaya Menuju Ekonomi Sirkular - Yuliati Yuliati; Hadi Santosa; Setiyadi Setiyadi; Suratno Lourentius (Jurnal Ilmiah Pangabdhi, 2021)
Waste processing activities through the 3R program (reduce, reuse and recycle) must be accompanied by reducing the volume/amount of waste itself. One way is to process waste starting from the source, among others, from dry leaf waste around our home environment. Community assistance activities in the use of dry leaves in the manufacture of charcoal briquettes as an alternative energy for environmental facilitators and Surabaya residents have been successfully carried out. The response of the residents was very positive and very enthusiastic in participating in this activity. The stages of implementing activities through workshops, training and mentoring are carried out in the form of lectures, questions and answers and direct practice in making briquettes. The results obtained in this community service are the formation of three superior briquette villages, namely Babat Jerawat, Tembok Gede and Ondomohen. The residents independently have succeeded in designing and making their own briquette printing equipment by utilizing used goods around them and making charcoal briquettes from dry leaves or burnt coconut shell charcoal and even has succeeded in marketing it even though it is still within the scope of the closest neighbors. Education about business prospects and marketing strategies was also given during training in empowering urban communities and responding to existing business opportunities and prospects so that they had a circular economy impact for community members to improve family welfare.